Varied Clinical Presentation and Management of Calvarial Metastases - Gupta, Sweety; Sharma, Gaurav; Sajeevan, Sanjay; Raut, Sagar N.; Ahuja, Rachit; Joseph, Deepa; Gupta, Amit; Gupta, Manoj (Asian Journal of Neurosurgery, 2022)
Calvarium and skull base can be affected by a variety of benign, tumor-like, and malignant processes. Skull metastases (SMs) may be located in any layer of the skull and may be incidental or present with neurological symptoms during the diagnostic workup. In the present study, we discuss the occurrence of SMs from various index malignancies and their myriad clinical presentation. This data-based study includes patients of bone metastases between June 2018 and July 2020. Patients with skull bone metastases were recognized, and location of primary site, their clinical presentation, and management strategy were noted. Ten patients with skull bone metastases were identified during this period. Four patients had skull base location with clinical manifestation as syndromes. Six patients had primary from breast cancer, three from Ewing's sarcoma, and one from lung cancer. Management varied according to the primary site and symptoms of each patient. SM, though not rare, is often diagnosed incidentally but presents diagnostic and management challenges in the patient with cancer.
Keywords: calvarial; metastases; skull base; disseminated disease